2022
DOI: 10.1038/s41467-022-30779-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Holliday junction sequence and dynamics on DNA crystal self-assembly

Abstract: The programmable synthesis of rationally engineered crystal architectures for the precise arrangement of molecular species is a foundational goal in nanotechnology, and DNA has become one of the most prominent molecules for the construction of these materials. In particular, branched DNA junctions have been used as the central building block for the assembly of 3D lattices. Here, crystallography is used to probe the effect of all 36 immobile Holliday junction sequences on self-assembling DNA crystals. Contrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 78 publications
1
53
0
Order By: Relevance
“…Specifically, regular junctions are geometrically driven by stacking interactions between opposing helices . Alteration of the junction sequence can be exploited by careful study to drive crossing angles with high precision, but inaccuracies can lead to torsion, bundling, or junction disruption in unanticipated ways . Presumably, the mesojunction design universe of DNA nanotechnology would be less dependent on stacking.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, regular junctions are geometrically driven by stacking interactions between opposing helices . Alteration of the junction sequence can be exploited by careful study to drive crossing angles with high precision, but inaccuracies can lead to torsion, bundling, or junction disruption in unanticipated ways . Presumably, the mesojunction design universe of DNA nanotechnology would be less dependent on stacking.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MD simulations of Holliday junctions have also been performed. 44,[57][58][59] Mathur et al has showed that MD simulations of dyes attached to the Holliday junctions of large DNA bundles can yield dye orientations in agreement with experimental uorescence data. 44 Wheatley et al found that isolated, four-arm Holliday junctions initialized in an open conformation stabilize in a stacked conguration at both high and low salt concentrations, indicating that MD is able to capture the conformational transitions of the Holliday junction.…”
Section: Introductionmentioning
confidence: 63%
“…Typical Holliday junction IDAs and twist angles fall in the range of ∼60° and ∼40–60°, respectively. 57–59,82 It should be noted that these values are for Holliday junctions without dyes attached to the DNA backbone – the dyes in our study act as an additional base or spacer in the DNA sequence, which may affect the DNA dynamics and conformations. This could lead to discrepancies observed between pure DNA Holliday junctions and Holliday junctions with dyes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations